2020
DOI: 10.2147/cia.s240400
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targetting Exosomes as a New Biomarker and Therapeutic Approach for Alzheimer’s Disease</p>

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease that mainly occurs in old age and involves progressive cognitive impairment. AD has become a major global issue for public health, with approximately 24 million people currently affected by the disease. Estimates indicted that this number will quadruple by 2050. Because of the high incidence of AD, there is an urgent need to develop new strategies to diagnose and treat AD. Many recent studies have indicated the multiple, yet somewhat controversial, roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 120 publications
(162 reference statements)
0
47
0
Order By: Relevance
“…Scientists remarkably consider exosomes owing to their roles in the progression of various diseases 49,50 . Discovering exosome biogenesis regulatory mechanisms can aid us to prevent or predict their detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists remarkably consider exosomes owing to their roles in the progression of various diseases 49,50 . Discovering exosome biogenesis regulatory mechanisms can aid us to prevent or predict their detrimental effects.…”
Section: Discussionmentioning
confidence: 99%
“…This molecule has been shown to be secreted and exported from cells by a novel, alternative secretory pathway including specific vesicles and/or exosomes [ 32 34 ]. Modulation of Gal-3 secretion by exosomes is an interesting concept and potential therapeutic approach because our recent review shows that naturally occurring or engineered exosomes derived from stem cells, or potentially other cell types, provide therapeutic effects in AD [ 35 , 36 ]. Moreover, recent experiments have shown that Gal-3 can shuttle between the cytoplasm and nucleus across the nuclear pore complex in a dynamic process [ 37 ].…”
Section: Main Textmentioning
confidence: 99%
“…They further showed that modification of BMEVs with folate could enhance tumor-targeting ability as compared to the free drug [ 133 ]. Recently, because many clinical trials for the treatment of Alzheimer’s disease (AD) using synthetic drugs have failed [ 136 , 137 , 138 ], scientists are trying to develop targeted delivery using EVs and developing precision medicine-loaded EVs for the treatment of AD [ 139 , 140 ]. Plant-derived traditional medicine have been studied in preclinical models of AD [ 141 , 142 , 143 ].…”
Section: How Crucial Is the Origin Of Exosomes For Drug Delivery?mentioning
confidence: 99%